PENGEMBANGAN PEMBELAJARAN BAHASA INDONESIA DI PERGURUAN TINGGI MENGGUNAKAN MEDIA LUAR RUANG - Sainil Amral; Sumiharti Sumiharti (Universitas Batanghari, 2025)
The purpose of this study was to describe the level of validity of teaching materials, lecturers' perceptions of teaching materials, and the level of effectiveness of teaching materials for Indonesian language learning in universities based on the outdoor media developed. This research was conducted at the Faculty of Economics, Batanghari University, Jambi, located in Jambi City. This research was conducted for 6 months, starting from April 2024 to September 2024. The object of the study was students of the Faculty of Economics, Even Semester, Batanghari University, Jambi, Academic Year 2023/2024. This study uses qualitative and quantitative research. The type of research is research and development in the field of education because it is used to develop and validate products in the field of learning that refer to the principles and steps of research and development put forward by Walter R. Borg and Gall (1983.775). Based on the table obtained, it can be concluded that learning by utilizing outdoor media can increase student activity and effectiveness in learning, statistical data on the t-test and the research results data table show that there is an increase in learning outcomes using outdoor media. The results of media expert data on the product were found to be 96%. This figure is included in the very good qualification and does not need to be revised. Furthermore, from the data from the material expert results, it was found that the figure was 97.5%. This figure is included in the very good qualification and does not need to be revised. Meanwhile, from the data from the responses of media experts, material experts, and lecturers' perceptions of the product, it was found that the figures were 96%, 97.5%, and 92.5%. This figure is included in the very good qualification and does not need to be revised.